Access 2016 advanced. - McCrae, Ed; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"Access 2016 Advanced will further build upon the topics covered in the Access 2016 Introduction and Intermediate courses. Students will review how to improve the structure of an Access database, maintain an Access database, create and modify Switchboards, configure security and multi-user environments, automate processes with VBA (Visual Basic for Applications), and use Table Events."--Resource description page.
Title from resource description page (Safari, viewed October 7, 2016).
Presenter, Ed McCrae.
Keywords: Microsoft Access; Database management; Electronic books